Legal implications governing medical negligence in India: creating awareness through six-dimensional framework of effective communication. Issue 5 (27th May 2020) - Sethi, Deepa; Arya, Vikas
Abstract : Purpose: The purpose of this study is to determine the existing legal implications for medical negligence in India and recommending how open communication and empathy by the doctors can help prevent these implications. Design/methodology/approach: This research is based on a qualitative method. Indian laws, Indian constitution, journal articles, books and other writings have been reviewed to develop this study. Findings: There are many legal implications for medical negligence in India, and justice can be demanded under a number of Indian laws. This study also found that it is important to create awareness regarding the laws governing medical negligence through effective communication and empathy. Originality/value: Extant literature discusses in detail the various laws related to medical negligence and few talk about creating awareness about these laws amongst people, and while some researchers understand the importance of sensitizing health professionals of the nitty-gritty of the legal implication governing medical negligence, none provides a framework of medical negligence with the help of sensitizing health professionals through communication. This study fills the gap by focusing on prevention than cure.